2017
DOI: 10.15420/ecr.2016:33:2
|View full text |Cite
|
Sign up to set email alerts
|

Women with Stable Angina Pectoris and No Obstructive Coronary Artery Disease: Closer to a Diagnosis

Abstract: A large proportion of women with chest pain have no obstructive coronary artery disease. Recent studies have demonstrated that these women continue to have symptoms and are at increased risk of cardiovascular morbidity and mortality. Coronary microvascular dysfunction (CMD) leads to an impairment of blood flow regulation to the myocardium and possible transient ischaemia. CMD is a disease entity with several pathophysiologic aspects and diagnostic modalities continue to be developed. However, due to the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 96 publications
(115 reference statements)
0
10
0
1
Order By: Relevance
“…For example, obese, one of the strong cardiovascular risk factor is more common in women (30%) than men (27%) (24). Several female related-factors have been shown to increase cardiac risk in women, such as oestrogen deficiency, polycystic ovary syndrome, premature menopause (26,27).Prior research also has suggested that women with CHD have a poor cardiovascular risk profile, which may contribute to the sex difference in morality after CHD (28). The Scottish Health Survey (24) showed the association between higher prevalence of multiple cardiovascular risk factors were particularly pronounced for women in most deprived quintiles (32%) compared with the least deprived quintiles (17%).…”
Section: Discussionmentioning
confidence: 99%
“…For example, obese, one of the strong cardiovascular risk factor is more common in women (30%) than men (27%) (24). Several female related-factors have been shown to increase cardiac risk in women, such as oestrogen deficiency, polycystic ovary syndrome, premature menopause (26,27).Prior research also has suggested that women with CHD have a poor cardiovascular risk profile, which may contribute to the sex difference in morality after CHD (28). The Scottish Health Survey (24) showed the association between higher prevalence of multiple cardiovascular risk factors were particularly pronounced for women in most deprived quintiles (32%) compared with the least deprived quintiles (17%).…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges of non-invasive functional imaging of microvascular function is that studies are typically aimed at investigating either the endothelial-dependent or non-endothelial-dependent pathway of CMD (not both pathways), possibly leading to an underestimation of the condition in the studied population. This might contribute to the wide range of reported prevalence of CMD across studied populations (Michelsen, Mygind, Frestad et al, 2017). Using dipyridamole and adenosine, we predominately assessed the non-endothelial-dependent pathway of coronary microvascular function.…”
Section: Association Between Mpr Angina and Cmdmentioning
confidence: 99%
“…Coronary microvascular dysfunction (CMD) is increasingly recognized as a cause of angina pectoris (AP) in patients without obstructive coronary artery disease (CAD) . CMD can be assessed noninvasively by transthoracic Doppler echocardiography (TTDE) with pharmacological stress as a significant reduction of the coronary flow velocity reserve (CFVR) in a major epicardial coronary artery (usually the left anterior descending artery [LAD]), and low CFVR has been shown to be an independent marker of adverse prognosis in a variety of patient subgroups, including in patients with AP without obstructive CAD …”
Section: Introductionmentioning
confidence: 99%